Food as medicine: A possible preventive measure against coronavirus disease (COVID‐19). (21st July 2020) - Yang, Fan; Zhang, Yue; Tariq, Akash; Jiang, Xiaolan; Ahmed, Zeeshan; Zhihao, Zhang; Idrees, Muhammad; Azizullah, Azizullah; Adnan, Muhammad; Bussmann, Rainer W.
Abstract : The recent and ongoing outbreak of coronavirus disease (COVID‐19) is a huge global challenge. The outbreak, which first occurred in Wuhan City, Hubei Province, China and then rapidly spread to other provinces and to more than 200 countries abroad, has been declared a global pandemic by the World Health Organization. Those with compromised immune systems and/or existing respiratory, metabolic or cardiac problems are more susceptible to the infection and are at higher risk of serious illness or even death. The present review was designed to report important functional food plants with immunomodulatory and anti‐viral properties. Data on medicinal food plants were retrieved and downloaded from English‐language journals using online search engines. The functional food plants herein documented might not only enhance the immune system and cure respiratory tract infections but can also greatly impact the overall health of the general public. As many people in the world are now confined to their homes, inclusion of these easily accessible plants in the daily diet may help to strengthen the immune system and guard against infection by SARS‐CoV‐2. This might reduce the risk of COVID‐19 and initiate a rapid recovery in cases of SARS‐CoV‐2 infection.